The Impact of Household Food Consumption Data Collection Methods on Poverty and Inequality Measures in Niger - Backiny-Yetna, Prospere; Steele, Diane; Yacoubou Djima, Ismael (World Bank Group, Washington, DC, 2014)
This paper assesses the impact of three methodologies of food data collection on the welfare distribution, and poverty and inequality measures in Niger. The first methodology is a 7-day recall period, the second one is a usual month, and the third one is a 7-day diary. The paper finds that there is a difference in the distribution of welfare between, on the one hand, the two first methodologies (7-day recall and a usual month, which give results close to each other) and, on the other hand, the 7-day diary method. When considering annual per capita consumption, the 7-day diary lags the 7-day recall by 28 percent. This gap is not only at the mean of the distribution, it has been found at any level. These differences lead to differences in poverty and inequality measures even when alternate poverty lines are used. This study underscores the problem that many developing countries face when it comes to monitoring poverty indicators over time where different methodologies have been used over the years.